2007
DOI: 10.1002/glia.20510
|View full text |Cite
|
Sign up to set email alerts
|

Reduced raft‐association of NF155 in active MS‐lesions is accompanied by the disruption of the paranodal junction

Abstract: Neurofascin155 (NF155) is required for the establishment of the paranodal axo-glial junction, the predominant interaction site between myelin and axon. It has been shown that the distribution of NF155 is altered in demyelinating diseases such as multiple sclerosis (MS). However, little is known about the biochemical mechanisms underlying these changes. We therefore compared NF155 in postmortem tissue of active and chronic inactive MS lesions with white matter from healthy controls. Although NF155 showed a very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…Early in the disease course and preceding demyelination, changes in the distribution of NF155 have been observed in MS lesions [Vyshkina1 & Kalman, 2008]. Maier et al [2007] showed that the NF155-levels were reduced, suggesting that NF155 is subject to protein degradation in the lesions. On the other hand, studies in sera showed levels significantly higher in patients with chronic progressive forms of MS compared to other inflammatory neurological diseases.…”
Section: Axolemma-enriched Fractionsmentioning
confidence: 99%
“…Early in the disease course and preceding demyelination, changes in the distribution of NF155 have been observed in MS lesions [Vyshkina1 & Kalman, 2008]. Maier et al [2007] showed that the NF155-levels were reduced, suggesting that NF155 is subject to protein degradation in the lesions. On the other hand, studies in sera showed levels significantly higher in patients with chronic progressive forms of MS compared to other inflammatory neurological diseases.…”
Section: Axolemma-enriched Fractionsmentioning
confidence: 99%
“…In contrast, mitochondria located in the axoplasm outside this region appeared normal, suggesting that the PJB influences mitochondrial function and perhaps transport in the axoplasm of the nodal/paranodal region of myelinated axons of peripheral nerves. The distribution of neurofascin 155 in the glial membrane is altered in one form of multiple sclerosis (MS), a demyelinating disease (Maier et al, 2007). This group discovered that efficient association of neurofascin 155 with lipid raft domains is required for the maintenance of the paranodal axo-glial junction and without this junction, demyelination occurs in MS.…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies to NF155 found in some patients with AIDP and patients with CIDP could be pathogenic only if their target at the paranodes becomes accessible. Since a disruption of paranodal architecture is a feature of different nerve pathologies such as ischemia and inflammation, 27,28 these antibodies could contribute to the pathology. Anti-NF155 antibodies were reported to inhibit myelination by blocking the formation of the Caspr/contactin/NF155 complex, the core structure at paranodal loops for adhesion between axon and glial cell.…”
mentioning
confidence: 99%